U.S. STRATEGY AND POLICY IN CENTRAL ASIA - LAUMULIN, Murat (CENTRAL ASIA AND THE CAUCASUS, 2007)
It goes without saying that American geopolitics and geostrategy are of a genuinely global nature and affect practically every region and every country. And Central Asia is no exception in this respect. America’s influence there is of a multi-factoral and multi-level nature in every aspect—the political, military-strategic, economic, and ideological. From the very first days of independence, the Central Asian countries have been aware of America’s influence (and pressure) in essentially every sphere. In Central Asia, America is confronted with other world centers of power (Russia, China, the EU, Iran, and other Islamic states), which explains the fairly frequent contradictions. American pol icy in Central Asia depends to a certain extent on Washington’s relations with these states, but it is not determined by them. On the whole, Central Asia’s policy is part of the U.S.’s broader Eurasian strategy, which covers the Caspian, the Caucasus, Russia, Afghanistan, the Middle East, South Asia, and China. It should also be said that America’s Eurasian policy is part of Washington’s much broader global strategy designed to perpetuate America’s domination in the world economic and financial system and its military-strategic superiority. America is seeking greater geopolitical influence (in Eurasia among other places) and containment of potential rivals (China, the EU, and Russia), as well as struggling against so-called international terrorism (for control over the Islamic world). Central Asia is an important, but not the only, element of the U.S.’s global strategy. At the same time, it is critically important for the U.S.’s Eurasian geopolitics to establish control over Eurasia. For this reason, Central Asia’s role and importance for Washington will become even greater